ENSURING COORDINATION OF INTERREGIONAL COOPERATION AND INVESTMENT INNOVATIVE ACTIVITY (Economics and region, 2021)
The study shows that there is the increase in foreign direct investment by type of economic activity to identify increased investment attractiveness. It is investigated that the trend of efficiency of foreign direct investment in Ukraine in relation to economic development is negative for revealing the level of economic development. Article analyzes the growth of the ratio of foreign direct investment per capita in percent in order to identify the need to increase the international investment attractiveness of Ukraine. Author considers that to increase the level of foreign investment it is necessary to promote the development of interregional cooperation: economic growth, decent working conditions, implement quality education, information-communication technologies, tourism development, foreign trade, agricultural sector, construction development, transport infrastructure, personnel training, development of industry and energy.
Keywords: investment; investment attractiveness; interregional cooperation; investment-innovative activity; gross domestic product